Analysis of Human Capital in Talent Management Program, Training and Development to Improve Employee Competence Case Study in BSG Group - Prastiyo Diatmono; Siti Mariam; Abdul Haeba Ramli (Universitas Trisakti, 2020)
The purpose of this research was to understand human capital analysis to talent management program, training and development to improvement employees competency. It was a qualitative research with an case study method conduct at BSG Group (6 companies) in 2019. The data were collected through participant observation using interview, observation, document study, and recording. The data analysis to understand management program was run with the company to make strategic changes to improve employees competency approach to human capital, including: (1) talent management, (2) training and development, using balance scorecard as measurement quality. The findings lead to the recommendation to make change talent management program, training and development to enhancement employees competency in linking the company's business strategy that can create an increase job productivity and company profits in accordance with the intended purpose the support and commitment of top management and empower to all employees synergistically.